A catalyst and its preparation method and application
By including molybdenum, bismuth, iron and cobalt in the catalyst, and controlling the specific diffraction peak relationship in its X-ray diffraction spectrum, combined with spray drying and sintering technology, the problem of easy pulverization and reduced activity of the catalyst at high aerial speed is solved, and the effects of high intensity, long life and high conversion are achieved.
Patent Information
- Application Number
- CN202411928875.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
AI Technical Summary
Existing catalysts are prone to powder and breakage when used at high aerial speeds, resulting in a shortening of life. Excessive mechanical forces during molding will affect the distribution of active components and crystal structure, affecting the activity and stability of the catalyst.
By including the metal elements molybdenum, bismuth, iron and cobalt in the catalyst and controlling the specific diffraction peak relationship in its X-ray diffraction spectrum, combined with spray drying and sintering techniques, a catalyst with high intensity, activity and stability was prepared.
The high strength and long life of the catalyst are achieved, while the conversion and yield of unsaturated aldehydes are improved, ensuring the stability of the catalyst used at high aerial speeds.
Smart Images

Figure CN119746878A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts and relates to a catalyst, in particular to a catalyst and a preparation method and application thereof. Background Art
[0002] The production of unsaturated aldehydes with olefins as raw materials under the action of catalysts has gradually been industrialized. For example, isobutylene and tert-butyl alcohol are used as raw materials to produce methacrolein. Among them, the activity, selectivity and stability of the catalyst are the key to ensure the smooth progress of the reaction. At present, the commonly used catalyst is mainly Mo-Bi composite metal oxide catalyst. In industrial production, the operating space velocity of the reaction device is often 1000-1200h -1 When running for a long period at such a high space velocity, the catalyst is very likely to be pulverized and broken during operation, resulting in a shortened catalyst life. Therefore, in practical applications, the catalyst is often required to have a higher strength.
[0003] The strength of the catalyst depends largely on the mechanical force applied to the material including the active components during the molding process. For example, in the molding process of coating, a high-strength catalyst is often obtained by using a large-diameter coating pan, increasing the rotation speed of the turntable in the pan, and extending the coating time. However, such a molding method often causes the material including the active components to be squeezed and crushed during the molding process, changing the distribution of the active components therein, affecting the crystal structure of the catalyst, and thus affecting the activity and stability of the catalyst.
[0004] Therefore, how to ensure the activity and stability of the catalyst while improving the catalyst strength is an urgent problem to be solved in this field. Summary of the invention
[0005] In view of the above-mentioned defects, the present invention provides a catalyst which not only has high strength but also has high activity and stability, can effectively extend the service life of the catalyst, and can achieve high conversion rate and yield in the preparation process of unsaturated aldehyde.
[0006] The present invention also provides a method for preparing the catalyst. The catalyst prepared by the method has high strength, catalytic activity and stability.
[0007] The present invention also provides a method for preparing an unsaturated aldehyde. The unsaturated aldehyde is prepared by using the above catalyst or the catalyst prepared by the above preparation method in a catalytic oxidation reaction to prepare an unsaturated aldehyde, thereby achieving a higher conversion rate and yield.
[0008] The first aspect of the present invention provides a catalyst, which includes an active component, wherein the active component contains at least the metal elements molybdenum, bismuth, iron and cobalt;
[0009] In the X-ray diffraction spectrum of the catalyst, there is a first diffraction peak at 26.50±0.2°, a second diffraction peak at 29.2±0.2°, and a third diffraction peak at 28.50±0.2°;
[0010] The peak intensity I of the first diffraction peak 1 and the peak intensity of the second diffraction peak I 2 Satisfaction: 4≤I 2 / I 1 ×100≤77, the peak intensity of the first diffraction peak is 1 and the peak intensity I of the third diffraction peak 3 Satisfy: 32≤I 3 / I 1 ×100≤274;
[0011] The attrition rate of the catalyst is no higher than 2.5%.
[0012] The catalyst as described above, wherein the catalyst comprises an active component composition as shown in Formula 1,
[0013] Mo 12 Bi b Fe c Co d X e Y f O g Formula 1
[0014] In Formula 1, Mo, Bi, Fe, Co, and O represent the elements molybdenum, bismuth, iron, cobalt, and oxygen, respectively; X includes at least one of nickel, zinc, tungsten, cerium, titanium, and manganese; and Y includes at least one of sodium, potassium, rubidium, cesium, and thallium; b, c, d, e, f, and g represent the atomic numbers of Bi, Fe, Co, X, Y, and O, respectively, wherein 0<b<7.5, 0<c<6.5, 2<d<11, 0.1<e<11, 0<f<3.5, and g=a value determined by the oxidation state of each element.
[0015] The catalyst as described above, wherein the catalyst comprises a carrier and a coating layer supported on at least a portion of the surface of the carrier, and the coating layer comprises an active component;
[0016] Preferably, the carrier comprises at least one of aluminum oxide, silicon oxide, and a silicon-aluminum composite material;
[0017] Preferably, the average particle size of the carrier is 3.60-4.30 mm;
[0018] Preferably, the mass percentage of the coating layer in the catalyst is 10-70wt%.
[0019] The catalyst as described above, wherein the average particle size of the catalyst is 4.40-4.50 mm, and / or the thickness of the coating layer is 0.10-0.90 mm.
[0020] The second aspect of the present invention provides a method for preparing the above catalyst, comprising the following steps:
[0021] At a temperature of 5-20° C. and a pressure of 1.01-10 atm, a precursor aqueous solution including at least a molybdenum source, a bismuth source, an iron source and a cobalt source is subjected to a precipitation reaction under stirring conditions at a stirring speed of 100-500 r / min to obtain a precipitation slurry;
[0022] The precipitation slurry is subjected to aging treatment under the conditions of a pressure of 1.01-10 atm and a temperature of 50-100° C. to obtain an aged slurry;
[0023] The aged slurry is spray-dried to obtain a spray material, and the weight loss rate of the spray material after calcination at 450-500° C. is controlled to be 20-45wt%; the spray material is first sintered at a sintering temperature of 300-550° C. and a heat preservation time of 2-15 hours to obtain a first product;
[0024] The first product is mixed with polysaccharide at a mass ratio of 1:(0.001-0.15) to obtain a mixed material; the mixed material is molded to obtain a molded product; the molded product is subjected to a second sintering at a sintering temperature of 400-600°C and a heat preservation time of 2-10h to obtain the catalyst.
[0025] The preparation method as described above, wherein the average particle size of the spray material is 5-300 μm;
[0026] And / or, the outlet temperature of the spray drying process is 95-165°C.
[0027] The preparation method as described above, wherein the molding method includes any one of tableting molding, extrusion molding, and coating molding;
[0028] Preferably, the molding method is coating molding.
[0029] The preparation method as described above, wherein the mixed material further comprises a binder; the binder comprises at least one of water, methanol, ethanol, ethylene glycol, and glycerol;
[0030] The preparation method as described above, wherein the polysaccharide includes homogeneous polysaccharide and / or heterogeneous polysaccharide; the homogeneous polysaccharide includes at least one of starch, glycogen, and microcrystalline cellulose; and the heterogeneous polysaccharide includes gum arabic and / or hyaluronic acid.
[0031] The third aspect of the present invention provides a method for preparing an unsaturated aldehyde, wherein the catalyst of the first aspect or the catalyst prepared by the preparation method of the second aspect is used in a catalytic oxidation reaction to prepare an unsaturated aldehyde, thereby preparing the unsaturated aldehyde.
[0032] The present invention makes the catalyst include at least metal elements of molybdenum, bismuth, iron and cobalt, and controls the X-ray diffraction spectrum of the catalyst to have a first diffraction peak with 2θ of 26.50±0.2°, a second diffraction peak with 2θ of 29.2±0.2° and a third diffraction peak with 2θ of 28.50±0.2°, and the peak intensity I of the first diffraction peak is 1 and the peak intensity of the second diffraction peak I 2 Satisfaction: 4≤I 2 / I 1 ×100≤77, peak intensity of the first diffraction peak I 1 and the peak intensity I of the third diffraction peak 3 Satisfy: 32≤I 3 / I 1 ×100≤274, so that the catalyst has high activity and stability; at the same time, the attrition rate of the catalyst is not higher than 2.5%, and it has high strength, which can effectively improve the service life of the catalyst. The catalyst is used in the catalytic oxidation reaction to prepare unsaturated aldehydes, which can achieve a high conversion rate and yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 This is the XRD diagram of the catalyst in Example 1 of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0035] Based on the production conditions of unsaturated aldehydes, higher requirements are placed on the strength of the catalyst. At present, the strength of the catalyst is generally improved by increasing the mechanical force applied to the material including the active component during the catalyst molding process. However, this molding method will cause the material including the active component to be crushed, which will cause the distribution of the active component to change, affecting the crystal structure of the catalyst in the subsequent sintering process, thereby having a negative impact on the activity and stability of the catalyst.
[0036] The inventor creatively discovered that by making the catalyst include active components of molybdenum, bismuth, iron, and cobalt, and making the XRD spectrum of the catalyst contain a diffraction peak of 2θ of 26.50±0.2° (first diffraction peak), a diffraction peak of 2θ of 28.5±0.2° (third diffraction peak), and a diffraction peak of 2θ of 29.2±0.2° (second diffraction peak), and controlling the three diffraction peaks to satisfy a specific relationship, not only can the catalyst have a higher strength, but also its reaction activity and stability can be effectively improved. After analysis, the inventor found that this is mainly because:
[0037] In the XRD spectrum, the diffraction peak at 2θ of 26.50±0.2° represents the composite carriers iron molybdate and cobalt molybdate, the diffraction peak at 2θ of 29.2±0.2° represents the inactive substance bismuth molybdate, and the diffraction peak at 2θ of 28.5±0.2° represents the active substance molybdenum bismuth iron cobalt.
[0038] Among them, the inactive substance bismuth molybdate is beneficial to improving stability, and the active substance molybdenum bismuth iron cobalt is beneficial to improving the reaction activity of the catalyst. During the sintering process of the catalyst, the molybdenum and bismuth in bismuth molybdate will migrate and combine with the iron and cobalt in the composite carrier to form the active substance molybdenum bismuth iron cobalt. It can be seen that the diffraction peak with 2θ of 29.2±0.2° and the diffraction peak with 2θ of 28.5±0.2° are mutually transformed and the relationship of one rising and the other falling is mutually exclusive. Therefore, if a balance between catalyst stability and activity is to be achieved, the peak intensities of the two diffraction peaks need to satisfy a certain relationship.
[0039] In addition, the active substance in the catalyst actually contains oxygen atoms. In the preparation process of unsaturated aldehydes, the oxygen atoms therein play the role of activating the reaction raw materials. For example, in the reaction system of preparing methacrolein with tert-butyl alcohol as the raw material, tert-butyl alcohol is dehydrated to form isobutylene, and isobutylene is generated under the action of the catalyst to form methacrolein, where the oxygen atoms in methacrolein come from the oxygen in the active substance; therefore, after the active substance loses oxygen, it cannot activate the reaction raw materials. The iron and cobalt in the carrier can activate oxygen, replenish the oxygen in the active substance, and restore its oxidation activity, thereby realizing the normal reaction of the catalyst. Therefore, if the catalyst is to be able to function for a long time and have high stability and activity, the iron and cobalt in the composite carrier are also indispensable.
[0040] Therefore, when the above three diffraction peaks exist in the XRD spectrum of the catalyst and satisfy a specific relationship, the catalyst can have both high activity and stability.
[0041] Based on the above analysis, the first aspect of the present invention provides a catalyst, which includes an active component, and the active component contains at least the metal elements molybdenum, bismuth, iron and cobalt;
[0042] In the X-ray diffraction spectrum of the catalyst, there is a first diffraction peak at 26.50±0.2°, a second diffraction peak at 29.2±0.2°, and a third diffraction peak at 28.50±0.2°;
[0043] The peak intensity of the first diffraction peak is I 1 and the peak intensity of the second diffraction peak I 2 Satisfaction: 4≤I 2 / I 1 ×100≤77, peak intensity of the first diffraction peak I 1 and the peak intensity of the third diffraction peak I 3 Satisfy: 32≤I 3 / I 1 ×100≤274;
[0044] The attrition rate of the catalyst is no higher than 2.5%.
[0045] When the catalyst satisfies the above-mentioned relationship, more molybdenum and bismuth in the bismuth molybdate grains migrate during the high-temperature sintering process, combine with iron and cobalt, and generate more active molybdenum bismuth iron cobalt;At the same time, bismuth molybdate grains also undergo a certain degree of sintering during the sintering process, which is conducive to improving the stability of the catalyst, achieving a balance between stability and activity, so that the catalyst has high stability and reactivity at the same time;In addition, the catalyst contains enough composite carriers of cobalt molybdate and iron molybdate, providing enough oxygen for the active material to ensure the normal progress of the unsaturated aldehyde preparation reaction. Moreover, the attrition rate of the catalyst is not higher than 2.5%, indicating that the catalyst has a higher strength, and can effectively avoid the catalyst from peeling off active powder during the reaction of unsaturated aldehydes, affecting its service life. Thus, the catalyst in the present invention not only has a higher strength, but also has a higher reactivity and stability, effectively improving the yield and raw material conversion rate of unsaturated aldehydes.
[0046] For example, I 2 / I 1 ×100 is 4, 9, 14, 19, 24, 29, 34, 39, 44, 49, 54, 59, 64, 69, 74 or 77.
[0047] For example, I 3 / I 1 ×100 is 32, 52, 72, 92, 112, 132, 152, 172, 192, 212, 232, 252 or 274.
[0048] The present invention does not impose any specific restrictions on the composition of the active components in the catalyst, and it only needs to contain molybdenum, bismuth, iron and cobalt.
[0049] The "wear rate" in the present invention is obtained by testing including the following methods:
[0050] The attrition rate of the catalyst was measured by an attrition tester, which included a stainless steel cylinder with an inner diameter of 15 cm and a baffle with a height of 1.5 cm installed on the inner wall of the cylinder. 1 The catalyst is placed in a cylinder, the cylinder is sealed, and then the cylinder is rotated at a speed of 60 rpm for 15 minutes. After the rotation, the catalyst in the barrel is taken out and sieved with a stainless steel sieve with a pore size of 1 mm. The residual catalyst left on the sieve after the sieving is weighed to obtain the mass m 2 ; The attrition rate of the catalyst is: (m 1 -m 2 ) / m 1 ×100%.
[0051] In order to further improve the activity and stability of the catalyst, the composition of the active ingredients in the catalyst can also be adjusted.
[0052] In one embodiment, the catalyst comprises an active component composition as shown in Formula 1,
[0053] Mo 12 Bi b Fe c Co d X e Y f O g Formula 1
[0054] In Formula 1, Mo, Bi, Fe, Co, and O represent the elements molybdenum, bismuth, iron, cobalt, and oxygen, respectively; X includes at least one of nickel, zinc, tungsten, cerium, titanium, and manganese; and Y includes at least one of sodium, potassium, rubidium, cesium, and thallium; b, c, d, e, f, and g represent the atomic numbers of Bi, Fe, Co, X, Y, and O, respectively, wherein 0<b<7.5, 0<c<6.5, 2<d<11, 0.1<e<11, 0<f<3.5, and g=a value determined by the oxidation state of each element.
[0055] When the catalyst includes the active component composition shown in Formula 1, the activity and stability of the catalyst can be further improved, so that the catalyst can achieve a higher conversion rate and unsaturated aldehyde yield during a long reaction process.
[0056] Of course, the structure of the catalyst can be further adjusted, for example, the composition of the catalyst, the average particle size of the carrier, the mass content of the coating layer in the catalyst, the average particle size of the catalyst and the thickness of the coating layer, etc., to further improve the performance of the catalyst.
[0057] Among them, by adjusting the catalyst composition, heat accumulation in the catalyst bed can be avoided to cause temperature runaway, which is beneficial to prolonging the catalyst life and improving the selectivity of unsaturated aldehydes.
[0058] By adjusting the average particle size of the carrier, the catalyst can be better loaded into the reaction device and have good contact with the reactants, which is beneficial to improving the degree of reaction.
[0059] By adjusting the mass content of the coating layer in the catalyst, the content of active components in the catalyst can be further controlled to avoid negative effects on the reaction caused by excessive or insufficient content.
[0060] By adjusting the average particle size of the catalyst and the thickness of the coating layer, the service life of the catalyst can be extended and the stability of the catalyst can be improved.
[0061] In one embodiment, the catalyst includes a carrier and a coating layer supported on at least a portion of the surface of the carrier, and the coating layer includes an active component;
[0062] Preferably, the carrier comprises at least one of aluminum oxide, silicon oxide, and a silicon-aluminum composite material.
[0063] When the catalyst is a coated structure, the heat generated on the coating layer during the catalytic reaction can be transferred out by the carrier in a timely manner, avoiding heat accumulation that causes the catalyst bed to run hot, which is beneficial to preventing high-temperature sintering of the catalyst and the occurrence of side reactions at high temperatures.
[0064] Preferably, the average particle size of the carrier is 3.60-4.30 mm. When the diameter of the carrier is within the aforementioned range, the catalyst can be better applied to the tube reactor of an industrial device.
[0065] Illustratively, the average particle size of the carrier is 3.6 mm, 3.7 mm, 3.8 mm, 3.9 mm, 4.0 mm, 4.1 mm, 4.2 mm, or 4.3 mm.
[0066] The "average particle size of the carrier" in the present invention can be tested by the following method: take 200 carrier particles, use a vernier caliper to test the particle size of each carrier particle, and record the data. The average particle size of the carrier is the average value of the sizes of each carrier particle.
[0067] Preferably, the mass percentage of the coating layer in the catalyst is 10-70wt%, within this range, not only can the catalyst be guaranteed to have sufficient active components, but also the heat accumulation caused by excessive active components can be prevented, thus avoiding the catalyst bed from overheating.
[0068] Illustratively, the mass percentage of the coating layer in the catalyst is 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, 55wt%, 60wt%, 65wt% or 70wt%.
[0069] In a specific embodiment, the average particle size of the catalyst is 4.40-4.50 mm. Within this range, the service life of the catalyst can be further extended, ensuring that the catalyst can achieve a high yield of unsaturated aldehydes in a long reaction time.
[0070] Illustratively, the average particle size of the catalyst is 4.40 mm, 4.42 mm, 4.44 mm, 4.46 mm, 4.48 mm or 4.50 mm.
[0071] The "average particle size of the catalyst" in the present invention can be obtained by testing as follows: take 200 catalyst particles, use a vernier caliper to test the particle size of each catalyst particle, and record the data. The average particle size of the catalyst is the average value of the sizes of each catalyst particle.
[0072] In a specific embodiment, the thickness of the coating layer is 0.10-0.90 mm. Within this range, the stability of the catalyst during a long reaction period can be further improved, and the yield of the unsaturated aldehyde can be improved.
[0073] Exemplarily, the thickness of the coating layer is 0.10 mm, 0.20 mm, 0.30 mm, 0.40 mm, 0.50 mm, 0.60 mm, 0.70 mm, 0.80 mm, or 0.90 mm.
[0074] The second aspect of the present invention provides a method for preparing the catalyst of the first aspect, comprising the following steps:
[0075] At a temperature of 5-20° C. and a pressure of 1.01-10 atm, a precursor aqueous solution including at least a molybdenum source, a bismuth source, an iron source and a cobalt source is subjected to a precipitation reaction under stirring conditions at a stirring speed of 100-500 r / min to obtain a precipitation slurry;
[0076] The precipitated slurry is subjected to aging treatment under the conditions of a pressure of 1.01-10 atm and a temperature of 50-100° C. to obtain an aged slurry;
[0077] The aged slurry is spray-dried to obtain a spray material, and the weight loss rate of the spray material after calcination at 450-500° C. is controlled to be 20-45wt%; the spray material is first sintered at a sintering temperature of 300-550° C. and a heat preservation time of 2-15 hours to obtain a first product;
[0078] The first product and polysaccharide are mixed at a mass ratio of 1:(0.001-0.15) to obtain a mixed material; the mixed material is molded to obtain a molded product; the molded product is subjected to a second sintering at a sintering temperature of 400-600°C and a heat preservation time of 2-10h to obtain a catalyst.
[0079] Specifically, a precursor solution including at least a molybdenum source, a bismuth source, an iron source and a cobalt source is subjected to a precipitation reaction at a temperature of 5-20° C. and a pressure of 1.01-10 atm, and stirring is maintained during the reaction at a stirring speed of 100-500 r / min to obtain a precipitation slurry.
[0080] Then, the precipitation slurry is subjected to aging treatment. Specifically, after the precipitation reaction is completed, the reaction system is sealed, and the temperature of the reaction system is raised to 50-100°C. During the heating process, the pressure in the reaction system will gradually increase to reach positive pressure, or nitrogen is introduced into the closed reaction system during the heating process to make the system pressure reach positive pressure, and the system pressure is controlled to be 1.01-10atm. After the temperature reaches the set aging temperature, it is kept warm for a period of time to obtain the aged slurry.
[0081] The aged slurry is spray dried, and the outlet temperature is controlled so that the weight loss rate of the obtained spray material after calcination at 450-500°C is 20-45wt%; the spray material is then subjected to a first sintering to obtain a first product, and the first sintering temperature is controlled to be 300-550°C, and the insulation time is 2-15h.
[0082] The first product and polysaccharide are mixed at a mass ratio of 1:(0.001-0.15) to obtain a uniform mixed material; then, the mixed material is molded to obtain a molded product; under an air atmosphere, the molded product is subjected to a second sintering, the sintering temperature is controlled to be 400-600°C, and the insulation time is 2-10h to obtain a catalyst.
[0083] Illustratively, the precipitation reaction is carried out at a temperature of 5°C, 8°C, 11°C, 14°C, 17°C or 20°C, and at a pressure of 1.01 atm, 2 atm, 4 atm, 6 atm, 8 atm or 10 atm.
[0084] Illustratively, the pressure in the aging treatment is 1.01 atm, 2 atm, 4 atm, 6 atm, 8 atm or 10 atm; the temperature in the aging treatment is 50°C, 60°C, 70°C, 80°C, 90°C or 100°C.
[0085] Illustratively, the weight loss of the spray material after calcination at 450-500° C. is 20wt%, 25wt%, 30wt%, 35wt%, 40wt% or 45wt%.
[0086] Illustratively, the first sintering temperature is 300°C, 350°C, 400°C, 450°C, 500°C or 550°C; and the holding time is 2h, 4h, 6h, 8h, 10h, 12h or 15h.
[0087] Illustratively, the mass ratio of the first product to the polysaccharide is 1:0.001, 1:0.01, 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.10, 1:0.11, 1:0.12, 1:0.13, 1:0.14 or 1:0.15.
[0088] Illustratively, the second sintering temperature is 400° C., 450° C., 500° C., 550° C. or 600° C.; and the holding time is 2 h, 4 h, 6 h, 8 h or 10 h.
[0089] Furthermore, the precursor aqueous solution may also include an X source and / or a Y source.
[0090] Furthermore, the order of adding the solution including the molybdenum source, the solution including the bismuth source, the solution including the iron source and the solution including the cobalt source in the precipitation reaction can be adjusted to further enhance the activity and stability of the catalyst.
[0091] Specifically, a solution including a molybdenum source is used as the first precursor solution, a solution including an iron source and a cobalt source is used as the second precursor solution, and a solution including a bismuth source is used as the third precursor solution; at a temperature of 5-20°C, a pressure of 1.01-10atm, and a stirring speed of 100-500r / min, the second precursor solution is added to the first precursor solution to obtain a mixed slurry, and then the third precursor solution is added to the aforementioned mixed slurry to obtain a precipitation slurry.
[0092] Further, the Y source can be mixed with the molybdenum source to form a first precursor solution; and the X source can be mixed with the iron source and the cobalt source to form a second precursor solution.
[0093] Furthermore, stirring is maintained during the aging treatment, and the stirring speed may be kept consistent with the stirring speed during the precipitation reaction.
[0094] The present invention does not specifically limit the molar ratio of each metal element in the raw material. Further, the molar ratio of each metal element in the raw material can be controlled so that the catalyst includes the active component Mo 12 Bi b Fe c Co d X e Y f O g , where 0<b<7.5, 0<c<6.5, 2<d<11, 0.1<e<11, 0<f<3.5, g=the value determined by the oxidation state of each element.
[0095] The molybdenum source in the present invention refers to a raw material for providing the molybdenum element, the bismuth source refers to a raw material for providing the bismuth element, the iron source refers to a raw material for providing the iron element, the cobalt source refers to a raw material for providing the cobalt element, the X source refers to a raw material for providing the X element (nickel, zinc, tungsten, cerium, titanium, manganese), and the Y source refers to a raw material for providing the Y element (sodium, potassium, rubidium, cesium, thallium). As long as they contain the aforementioned target elements, they are all within the scope of the present invention.
[0096] Exemplarily, the molybdenum source, bismuth source, iron source, cobalt source, X source and Y source independently include at least one of nitrates, carbonates, organic acid salts and hydroxides. Among them, the molybdenum source includes at least one of molybdic acid, molybdenum trioxide and ammonium molybdate, preferably ammonium heptamolybdate; the bismuth source includes at least one of bismuth nitrate, bismuth carbonate and bismuth acetate, preferably bismuth nitrate; the iron source includes at least one of ferric nitrate nonahydrate, ferric acetate and ferric chloride, preferably ferric nitrate nonahydrate; the cobalt source includes at least one of cobalt nitrate hexahydrate, cobalt acetate and cobalt chloride, preferably cobalt nitrate hexahydrate.
[0097] The present invention does not specifically limit the sources of the molybdenum source, bismuth source, iron source, cobalt source, X source, and Y source, and any commercially available product or product prepared by a conventional preparation method known to those skilled in the art may be used.
[0098] The present invention does not specifically limit the adding speed of the second precursor solution and the adding speed of the third precursor solution. For example, the adding speed is 1-2000 g / min.
[0099] The present invention does not specifically limit the aging time. For example, the aging time is 0-20 hours.
[0100] The present invention does not impose any specific restrictions on the inlet temperature and outlet temperature of the spray drying process, and it is only necessary that the weight loss rate of the spray material after calcination at 450-500°C is within the aforementioned range.
[0101] The present invention does not specifically limit the mixing method, and it is only necessary to uniformly mix the first product and the polysaccharide. For example, a high-speed mixer can be used for mixing.
[0102] The present invention does not specifically limit the method of molding treatment. For example, any one of tableting molding, extrusion molding and coating molding can be adopted.
[0103] It can be understood that tableting refers to a method of placing the carrier and the first product powder in a closed mold of a certain shape, and applying external pressure to agglomerate and compress the powder; wherein the carrier can be a commonly used material in the art, such as inert alumina ceramic rings, graphite, etc. It is suitable for pressing conventional catalyst tablets in cylindrical and Raschig ring shapes, and is also suitable for the molding of special-shaped tablets such as gear shapes.
[0104] Extrusion molding means that after the first product powder and an appropriate amount of auxiliary agent are fully kneaded, the kneaded material is fed into an extruder, extruded under the action of external extrusion force, and then pelletized and shaped to obtain a catalyst product of a certain size; wherein the auxiliary agent can be a commonly used material in this field, such as pseudo-boehmite, silica sol, etc.
[0105] Coating molding refers to putting the carrier into a fixed cylinder at one time. The bottom plate of the cylinder is a rotating disc with a flat or uneven surface. During the molding process, the bottom plate rotates at a high speed so that the carrier can revolve and rotate at a high speed. Subsequently, the first product powder and polysaccharide are added to the cylinder at one time or intermittently to obtain a catalyst, which includes a carrier and a coating layer loaded on at least a part of the surface of the carrier.
[0106] The preparation method of the catalyst of the present invention firstly controls the stirring speed during the precipitation reaction and the aging process through a precipitation reaction to obtain a uniform precipitation material, thereby making the size of the bismuth molybdate crystals in the slurry after aging more appropriate, thereby avoiding excessive sintering between the bismuth molybdate crystals in the subsequent first sintering process, and making the molybdenum and bismuth in the bismuth molybdate migrate better, and combine with the iron and cobalt in the composite carrier to form an active substance molybdenum bismuth iron cobalt, thereby achieving a balance between stability and activity. At the same time, the weight loss rate of the spray material after calcination at 450-500° C. is controlled to be 20-45wt%, and the first product is obtained; by controlling the weight loss rate, the catalyst activity can be prevented from decreasing due to too low or too high water content in the spray material.
[0107] In addition, the present invention also mixes the first product obtained by the above sintering with polysaccharides. At this time, the polysaccharides are distributed between the active powders (i.e., the first product). After the molding process and the second sintering, the polysaccharides undergo a pyrolysis reaction to form gaps between the active powders, which play a role of physical isolation and prevent excessive sintering between the active powders due to excessive temperature under high-temperature roasting; and the mass ratio of the first product to the polysaccharide is controlled to be 1: (0.001-0.15) to prevent insufficient physical isolation due to too little polysaccharide, excessive sintering of active components, and affecting the activity of the catalyst; it can also avoid excessive isolation due to too much polysaccharide, resulting in insufficient sintering of the powder in the catalyst and reduced strength of the catalyst.
[0108] At the same time, since there are a large number of gaps between the active powders, the temperature of the second calcination can be increased to a certain extent. At this temperature (400-600°C), a certain degree of sintering occurs between the active powders, which is beneficial to improving the strength of the catalyst. However, this degree of sintering does not cause the grains in the catalyst to be too large or too small, and can ensure the high activity and high stability of the catalyst.
[0109] Therefore, through the aforementioned preparation method, a balance between strength and activity can be achieved, so that the catalyst has high strength, reaction activity and stability at the same time.
[0110] In a specific embodiment, the average particle size of the spray material is 5-300 μm. Within this range, not only can the excessive sintering between the bismuth molybdate grains during the second sintering process be effectively prevented, which affects the activity of the catalyst, but also the reduction in catalyst strength due to an excessively large average particle size can be avoided, thereby further improving the strength and reaction activity of the catalyst.
[0111] Exemplarily, the average particle size of the spray is 5 μm, 50 μm, 100 μm, 150 μm, 200 μm, 250 μm or 300 μm.
[0112] In a specific embodiment, the outlet temperature of the spray drying process is 95-165° C. Within this range, the weight loss rate of the spray material after calcination at 450-500° C. is 20-45wt%, thereby improving the activity of the catalyst.
[0113] Illustratively, the outlet temperature of the spray drying process is 95°C, 105°C, 115°C, 125°C, 135°C, 145°C, 155°C, or 165°C.
[0114] In a specific embodiment, the molding method includes any one of tablet molding, extrusion molding, and coating molding; preferably, the molding method is coating molding. When coating molding is selected for molding, a catalyst with a coated structure can be obtained, that is, it includes a carrier and a coating layer loaded on at least a part of the surface of the carrier, wherein the coating layer includes an active component. The catalyst with such a coated structure can enable the heat generated by the active component on the coating layer during the catalytic reaction to be transferred away by the carrier in a timely manner, avoiding heat accumulation and causing the catalyst bed to overheat, which can not only avoid high-temperature sintering of the catalyst, but also avoid the occurrence of side reactions at high temperatures.
[0115] The present invention does not specifically limit the parameters in the coating molding process. For example, the rotation speed of the pan during the coating molding process can be adjusted within the range of 20-500 rpm, and the feeding speed of the mixed material (i.e., the first product and the polysaccharide) can be adjusted within the range of 1-2000 g / min.
[0116] In a specific embodiment, the mixture further includes a binder; the binder includes at least one of water, methanol, ethanol, ethylene glycol, and glycerol. When the mixture further includes a binder, the molding effect and strength of the catalyst can be further improved.
[0117] Furthermore, when coating molding is adopted, the feed rate of the binder can be adjusted within the range of 1-2000 g / min.
[0118] Preferably, the binder is a glycerol aqueous solution with a mass concentration of 5% or more.
[0119] Preferably, the mass ratio of the first product to the binder is (3-4):1.
[0120] When the binder includes multiple compounds of the aforementioned compounds at the same time, the present invention does not impose any particular limitation on the ratio between the specific compounds.
[0121] The present invention does not specifically limit the source of the binder, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0122] In a specific embodiment, the polysaccharide includes homogeneous polysaccharide and / or heterogeneous polysaccharide; the homogeneous polysaccharide includes at least one of starch, glycogen, and microcrystalline cellulose; the heterogeneous polysaccharide includes gum arabic and / or hyaluronic acid.
[0123] When the polysaccharide includes multiple compounds of the aforementioned compounds at the same time, the present invention does not impose any particular limitation on the ratio between the specific compounds.
[0124] The present invention does not specifically limit the source of the polysaccharide, and any commercially available product or a product prepared by a conventional preparation method well known to those skilled in the art may be used.
[0125] The third aspect of the present invention provides a method for preparing an unsaturated aldehyde, wherein the catalyst of the first aspect or the catalyst prepared by the preparation method of the second aspect is used in a catalytic oxidation reaction to prepare an unsaturated aldehyde, thereby preparing the unsaturated aldehyde.
[0126] Since the catalyst used therein has high strength, reactivity and stability, the catalyst can be used in the catalytic oxidation reaction to prepare unsaturated aldehydes to effectively improve the conversion rate and yield.
[0127] The catalyst provided by the present invention will be specifically introduced below through specific examples.
[0128] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0129] Example 1
[0130] 1) 2807 parts by weight of ammonium heptamolybdate and 32.5 parts by weight of cesium carbonate were dissolved in 9800 parts by weight of pure water to obtain a first precursor solution; 1020 parts by weight of ferric nitrate nonahydrate, 2706 parts by weight of cobalt nitrate hexahydrate and 312 parts by weight of nickel nitrate hexahydrate were dissolved in 4000 parts by weight of pure water to obtain a second precursor solution; 900 parts by weight of bismuth nitrate pentahydrate were dissolved in 2550 parts by weight of nitric acid aqueous solution (concentration of 14%) to obtain a third precursor solution; at 1.01 atm, 10° C. and stirring (stirring speed of 300 r / min), the second precursor solution was first added to the first precursor solution at a uniform speed to obtain a mixed solution, and then the third precursor solution was added to the mixed solution at a uniform speed to obtain a precipitation slurry;
[0131] 2) transferring the above precipitation slurry to a closed system for positive pressure aging treatment, maintaining stirring during the aging process, the stirring speed is 300r / min, the pressure of the reaction system is controlled to be 2atm, the aging temperature is 80°C, the aging time is 3h, and the aged slurry is obtained;
[0132] 3) spray drying the aged slurry, controlling the inlet temperature to 300° C. and the outlet temperature to 140° C., so that the weight loss rate of the spray material after calcination at 500° C. is 26 wt %, and the atomization frequency conversion is controlled to 200 Hz, so that the average particle size of the spray material is 40 μm; then calcining the spray material at 450° C. for 4 h to obtain the first product;
[0133] 4) The first product and the polysaccharide microcrystalline cellulose are fully mixed at a mass ratio of 1:0.05 to obtain a mixed material; the mixed material is coated on the surface of a porcelain ball with a diameter of 4.0 mm in a coating molding manner with the assistance of a 10% mass concentration of glycerol aqueous solution (the ratio of the first product to the 10% glycerol aqueous solution is 3:1) to obtain a molded product, wherein the mass percentage of the first product in the molded product is 40wt%; the molded product is subjected to a second sintering in flowing air at a sintering temperature of 520°C and a sintering time of 4h to obtain a catalyst having an average particle size of 4.44mm and an active ingredient composition of Mo 12 Bi 1.4 Fe 1.9 Co 7.02 Ni 0.81 Cs 0.15 O x .
[0134] Example 2
[0135] The preparation method of the catalyst in this example is basically the same as that in Example 1, except that in step 4), microcrystalline cellulose is replaced by starch, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.43 mm.
[0136] Example 3
[0137] The preparation method of the catalyst in this example is basically the same as that in Example 1, except that in step 4), microcrystalline cellulose is replaced by glycogen, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.43 mm.
[0138] Example 4
[0139] The preparation method of the catalyst in this example is basically the same as that in Example 1, except that in step 4), microcrystalline cellulose is replaced by gum arabic, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.41 mm.
[0140] Example 5
[0141] The preparation method of the catalyst in this example is basically the same as that in Example 1, except that in step 4), microcrystalline cellulose is replaced by hyaluronic acid, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.41 mm.
[0142] Example 6
[0143] The preparation method of the catalyst in the embodiment is basically the same as that in Example 1, except that in step 4), the polysaccharide also includes gum arabic, and the mass ratio of the first product to the polysaccharide microcrystalline cellulose and gum arabic is 1:0.05:0.02, and the other factors remain unchanged. The average particle size of the prepared catalyst is 4.46 mm.
[0144] Example 7
[0145] The preparation method of the catalyst in the embodiment is basically the same as that in Example 1, except that in step 4), the polysaccharide also includes hyaluronic acid, and the mass ratio of the first product to the polysaccharide microcrystalline cellulose and hyaluronic acid is 1:0.05:0.02, and the others remain unchanged. The average particle size of the prepared catalyst is 4.45 mm.
[0146] Example 8
[0147] The preparation method of the catalyst in this embodiment is basically the same as that in Example 1, except that in step 4), microcrystalline cellulose is replaced by starch and gum arabic, and the mass ratio of the first product to starch and gum arabic is 1:0.05:0.02, and the other parameters remain unchanged. The average particle size of the prepared catalyst is 4.47 mm.
[0148] Example 9
[0149] The preparation method of the catalyst in this embodiment is basically the same as that in Example 1, except that in step 4), microcrystalline cellulose is replaced by starch and hyaluronic acid, and the mass ratio of the first product to starch and hyaluronic acid is 1:0.05:0.02. Other factors remain unchanged, and the average particle size of the prepared catalyst is 4.45 mm.
[0150] Example 10
[0151] The preparation method of the catalyst in this embodiment is basically the same as that in Example 1, except that in step 4), the mass ratio of the first product to microcrystalline cellulose is 1:0.001, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.4 mm.
[0152] Embodiment 11
[0153] The preparation method of the catalyst in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass ratio of the first product to microcrystalline cellulose is 1:0.15, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.5 mm.
[0154] Example 12
[0155] The preparation method of the catalyst in this embodiment is basically the same as that in Embodiment 1, except that in step 3), the outlet temperature of the spray drying is controlled to be 165°C, the weight loss rate of the spray material after calcination at 500°C is 20%, and the other parameters remain unchanged. The average particle size of the prepared catalyst is 4.44 mm.
[0156] Example 13
[0157] The preparation method of the catalyst in this embodiment is basically the same as that in Example 1, except that in step 3), the outlet temperature of the spray drying is controlled to be 95°C, the weight loss rate of the spray material after calcination at 500°C is 45%, and the other parameters remain unchanged. The average particle size of the prepared catalyst is 4.44 mm.
[0158] Comparative Example 1
[0159] The preparation method of the catalyst in this comparative example is basically the same as that in Example 1, except that in step 4), the mixed material does not contain polysaccharide, and the other conditions remain unchanged. The average particle size of the prepared catalyst is 4.41 mm.
[0160] Comparative Example 2
[0161] The preparation method of the catalyst in this comparative example is basically the same as that in Example 1, except that in step 3), the outlet temperature of the spray drying is controlled to be 170°C, the weight loss rate of the spray material after calcination at 500°C is 18%, and the other parameters remain unchanged. The average particle size of the prepared catalyst is 4.41 mm.
[0162] Comparative Example 3
[0163] The preparation method of the catalyst in this comparative example is basically the same as that in Example 1, except that in step 3), the outlet temperature of the spray drying is controlled to be 90°C, the weight loss rate of the spray material after calcination at 500°C is 47%, and the other factors remain unchanged. The average particle size of the prepared catalyst is 4.46 mm.
[0164] Comparative Example 4
[0165] The preparation method of the catalyst in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass ratio of the first product to microcrystalline cellulose is 1:0.0005, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.4 mm.
[0166] Comparative Example 5
[0167] The preparation method of the catalyst in this embodiment is basically the same as that in Embodiment 1, except that in step 4), the mass ratio of the first product to microcrystalline cellulose is 1:0.6, and the other parts remain unchanged. The average particle size of the prepared catalyst is 4.62 mm.
[0168] Test example
[0169] 1. The average particle size and coating thickness of the catalysts prepared in the above examples and comparative examples were tested.
[0170] Catalyst average particle size test: Take 200 catalyst particles and use a vernier caliper to test the size of each catalyst particle. The average value of the sizes of all catalyst particles is the average particle size.
[0171] Carrier average particle size test: Take 200 carrier particles and use a vernier caliper to test the size of each carrier particle. The average value of the sizes of all carrier particles is the average particle size.
[0172] The thickness of the coating layer is the difference between the average particle size of the catalyst particles and the average particle size of the carrier particles.
[0173] The test results are shown in Table 1.
[0174] 2. The catalysts in the above embodiments and comparative examples were subjected to XRD testing and their attrition rates were tested, comprising the following steps:
[0175] 1) XRD test
[0176] The coating layer of the above catalyst was peeled off and ground into powder with a particle size of less than 10 μm. The powder was pressed into tablets to obtain a sample to be tested. A powder X-ray diffractometer with Cu Kα as an X-ray source was used to test the sample to be tested. The measurement range was 10°<2θ<35° and the measurement speed was 10° / min. The XRD spectrum of each catalyst was obtained. The base was deducted from the XRD spectrum to obtain the peak intensity value after the base was deducted, and then I was calculated. 2 / I 1 ×100 and I 3 / I 1 ×100, the calculation results are shown in Table 1 and Figure 1 , Figure 1 This is the XRD pattern of the catalyst in Example 1.
[0177] 2) Wear rate
[0178] The attrition rate of the catalyst was measured by an attrition tester, which included a stainless steel cylinder with an inner diameter of 15 cm and a baffle with a height of 1.5 cm installed on the inner wall of the cylinder. 1 The catalyst is placed in a cylinder, the cylinder is sealed, and then the cylinder is rotated at a speed of 60 rpm for 15 minutes. After the rotation, the catalyst in the barrel is taken out and sieved with a stainless steel sieve with a pore size of 3 mm. The residual catalyst left on the sieve after the sieving is weighed to obtain the mass m 2 ; The attrition rate of the catalyst is: (m 1 -m 2 ) / m 1 ×100%, the calculation results are shown in Table 1.
[0179] 2. The catalysts in the above embodiments and comparative examples are used in the preparation of unsaturated aldehydes, which specifically includes the following steps:
[0180] Tert-butyl alcohol, air, nitrogen and water are used as the reaction raw materials. By controlling the feed amount of each raw material, the molar ratio of each raw material before entering the reaction is: isobutylene (obtained by dehydration of tert-butyl alcohol): oxygen: nitrogen: water = 1:2:12:1.5, the reaction temperature is 360°C, and the space velocity is 1000h -1 ; Gas chromatography was used to analyze the isobutylene, oxygen, nitrogen, CO before and after the reaction. x The conversion rate of isobutylene and the yield of methacrolein are calculated based on the test results:
[0181] Isobutylene conversion rate (%) = (molar amount of isobutylene before reaction - molar amount of isobutylene after reaction) / molar amount of isobutylene before reaction × 100%;
[0182] Methacrolein yield (%) = (molar amount of methacrolein in the product) / (molar amount of isobutylene before reaction - molar amount after reaction) × 100%;
[0183] The calculation results are shown in Table 1.
[0184] Table 1
[0185]
[0186] From Table 1, we can see that:
[0187] Compared with Comparative Examples 1 to 5, the attrition rates of the catalysts in Examples 1 to 13 are all less than 2.5%, and I 2 / I 1 ×100 is between 4 and 77, I 3 / I 1 ×100 are all between 32 and 274, and correspondingly, a higher conversion rate and yield can be achieved in the reaction process. Specifically, the conversion rate of tert-butyl alcohol in Example 1 is as high as 99.73%, and the yield of methacrolein is as high as 84.12%, which are significantly higher than those of Comparative Examples 1 to 5. It can be seen that the catalyst in the present invention not only has a higher strength, but also has a higher activity and stability, can effectively improve the service life of the catalyst, and can achieve a higher conversion rate and yield in the preparation process of unsaturated aldehydes.
[0188] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A catalyst, characterized in that The catalyst includes active components, which contain at least metal elements of molybdenum, bismuth, iron and cobalt; In the X-ray diffraction spectrum of the catalyst, there is a first diffraction peak at 26.50±0.2°, a second diffraction peak at 29.2±0.2°, and a third diffraction peak at 28.50±0.2°; The peak intensity I1 of the first diffraction peak and the peak intensity I2 of the second diffraction peak satisfy: 4≤I2 / I1×100≤77, and the peak intensity I1 of the first diffraction peak and the peak intensity I3 of the third diffraction peak satisfy: 32≤I3 / I1×100≤274; The attrition rate of the catalyst is no higher than 2.5%.
2. The catalyst according to claim 1, characterized in that The catalyst comprises an active component composition as shown in Formula 1, Mo 12 Bi b Fe c Co d X e Y f O g Formula 1 In Formula 1, Mo, Bi, Fe, Co, and O represent the elements molybdenum, bismuth, iron, cobalt, and oxygen, respectively; X includes at least one of nickel, zinc, tungsten, cerium, titanium, and manganese; and Y includes at least one of sodium, potassium, rubidium, cesium, and thallium; b, c, d, e, f, and g represent the atomic numbers of Bi, Fe, Co, X, Y, and O, respectively, wherein 0<b<7.5, 0<c<6.5, 2<d<11, 0.1<e<11, 0<f<3.5, and g=a value determined by the oxidation state of each element.
3. The catalyst according to claim 1 or 2, characterized in that The catalyst comprises a carrier and a coating layer supported on at least a portion of the surface of the carrier, wherein the coating layer comprises an active component; Preferably, the carrier comprises at least one of aluminum oxide, silicon oxide, and a silicon-aluminum composite material; Preferably, the average particle size of the carrier is 3.60-4.30 mm; Preferably, the mass percentage of the coating layer in the catalyst is 10-70wt%.
4. The catalyst according to claim 3, characterized in that The average particle size of the catalyst is 4.40-4.50 mm, and / or the thickness of the coating layer is 0.10-0.90 mm.
5. A method for preparing the catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: At a temperature of 5-20° C. and a pressure of 1.01-10 atm, a precursor solution comprising at least a molybdenum source, a bismuth source, an iron source and a cobalt source is subjected to a precipitation reaction under stirring conditions at a stirring speed of 100-500 r / min to obtain a precipitation slurry; The precipitation slurry is subjected to aging treatment under the conditions of a pressure of 1.01-10 atm and a temperature of 50-100° C. to obtain an aged slurry; The aged slurry is spray-dried to obtain a spray material, and the weight loss rate of the spray material after calcination at 450-500° C. is controlled to be 20-45wt%; the spray material is first sintered at a sintering temperature of 300-550° C. and a heat preservation time of 2-15 hours to obtain a first product; The first product is mixed with polysaccharide at a mass ratio of 1:(0.001-0.15) to obtain a mixed material; the mixed material is molded to obtain a molded product; the molded product is subjected to a second sintering at a sintering temperature of 400-600°C and a heat preservation time of 2-10h to obtain the catalyst.
6. The method for preparing the catalyst according to claim 5, characterized in that: The average particle size of the spray material is 5-300 μm; And / or, the outlet temperature of the spray drying process is 95-165°C.
7. The method for preparing the catalyst according to claim 5 or 6, characterized in that: The molding method includes any one of tableting, extrusion, and coating; Preferably, the molding method is coating molding.
8. The method for preparing the catalyst according to any one of claims 5 to 7, characterized in that: The mixed material also includes a binder; the binder includes at least one of water, methanol, ethanol, ethylene glycol, and glycerol.
9. The method for preparing a catalyst according to any one of claims 5 to 8, characterized in that: The polysaccharide includes homogeneous polysaccharide and / or heterogeneous polysaccharide; the homogeneous polysaccharide includes at least one of starch, glycogen, and microcrystalline cellulose; the heterogeneous polysaccharide includes gum arabic and / or hyaluronic acid.
10. A method for preparing an unsaturated aldehyde, characterized in that: The catalyst described in any one of claims 1 to 4 or the catalyst prepared by the preparation method described in any one of claims 5 to 9 is used in the catalytic oxidation reaction to prepare unsaturated aldehyde to prepare unsaturated aldehyde.